The Solar Upper Transition Region Imager (SUTRI) Onboard the SATech-01 Satellite - Bai, Xianyong; Tian, Hui; Deng, Yuanyong; Wang, Zhanshan; Yang, Jianfeng; Zhang, Xiaofeng; Zhang, Yonghe; Qi, Runze; Wang, Nange; Gao, Yang; Yu, Jun; He, Chunling; et al. (Research in astronomy and astrophysics, 2023)
The Solar Upper Transition Region Imager (SUTRI) onboard the Space Advanced Technology demonstration satellite (SATech-01), which was launched to a Sun-synchronous orbit at a height of ∼500 km in 2022 July, aims to test the on-orbit performance of our newly developed Sc/Si multi-layer reflecting mirror and the 2k×2k EUV CMOS imaging camera and to take full-disk solar images at the Ne vii 46.5 nm spectral line with a filter width of ∼3 nm. SUTRI employs a Ritchey–Chrétien optical system with an aperture of 18 cm. The on-orbit observations show that SUTRI images have a field of view of ∼ 41.′6 × 41.′6 and a moderate spatial resolution of ∼8″ without an image stabilization system. The normal cadence of SUTRI images is 30 s and the solar observation time is about 16 hr each day because the earth eclipse time accounts for about 1/3 of SATech-01's orbit period. Approximately 15 GB data is acquired each day and made available online after processing. SUTRI images are valuable as the Ne vii 46.5 nm line is formed at a temperature regime of ∼0.5 MK in the solar atmosphere, which has rarely been sampled by existing solar imagers. SUTRI observations will establish connections between structures in the lower solar atmosphere and corona, and advance our understanding of various types of solar activity such as flares, filament eruptions, coronal jets and coronal mass ejections.